Emergence and Use of the Conjunctional Periphrasis no que: Grammaticalization, Polissemy and Argumentation - Longhin, Sanderleia Roberta (Univ Federal Minas Gerais, Fac Letras, 2015)
In this work I investigate junction constructions mobilized by the periphrasis no que, considering them as a recent instance of grammaticalization that contributes to enhance the conjunctional repertoire of Brazilian Portuguese. Based on no que data extracted from narrative texts, both from spoken and written enunciations, I seek to achieve two goals: (i) describe aspects of the no que constitution process as a periphrastic junctor, particularly with regard to the syntagmatic reanalysis and the emergence of meanings; and (ii) analyze the use conditions of no que with the purpose of elaborating on the argumentative maneuver which singularizes the junctor and helps understand its use motivations.
Keywords: Grammaticalization; Junction; Polyssemy; Argumentation